Cataract screening in a rural area of Southern China: a retrospective cohort study. (October 2016) - Tan, Xuhua; Lin, Haotian; Li, YuTing; Huang, Li; Zhu, Yi; Ni, Yao; Huang, WenYong; Liu, Yizhi
Abstract: Background: Cataract is the leading cause of blindness and impaired vision worldwide; however, cataract surgery rate in China (1300 cases per million people per year) is lower than in Europe, America, and India (greater than 5000 cases per million people per year). In the past 10 years, a public health screening system has been established for early diagnosis and intervention of chronic diseases such as diabetes and hypertension by the Disease Control and Prevention Centers (CDC) of China. The aim of this study was to investigate the effect of screening for cataract on surgery rates in Guangdong, China. Methods: Cataract screening was done by a non-profit eye hospital in the Zhao Qing area of Guangdong Province, together with public health screening by the local CDC. Demographic information, economic and education status, and rate of cataract surgery of the screening population were recorded. Awareness of cataract and access to ophthalmic examination and surgery were evaluated in randomly selected patients having surgery in villages by questionnaire. The study was approved by the ethics committee of Zhongshan Ophthalmic Center of Sun Yat-sen University. Written informed consent was obtained from each patient at the time of enrollment. Findings: From March 1, 2015, to March 31, 2016, we screened 24 254 people from five rural areas, 68 towns and 900 villages. Participants were aged 50–108 years (mean 73·9 [SD 8·6]), 16 128 (66·5%) were female, 3640 (15·0%) were from low income families, and 10 733 (44·3%) were illiterate. After screening, 20 724 (85·5%) participants were diagnosed with age-related cataracts, of which 8683 (41·9%) had visual acuity of 0·3 or less and were recommended for cataract surgery. Surgery was performed on 4612 (53·1%) recommended patients, of which 3978 (86·2%) were from villages, 330 (7·2%) were from towns, and 305 (6·6%) were from counties. Phacoemulsification was done on 3926 (85·1%) patients, and 686 (14·9%) had extracapsular cataract extraction. Implanted unfoldable intraocular lenses were provided to 3009 (72·3%) patients at no cost, and 1153 (27·7%) paid ¥1000 for foldable IOL implants. The uncorrected visual acuity of 2368 (51·3%) patients who had surgery was more than 0·5 at 1 month after surgery. The cataract surgery rate for the Zhao Qing area was 1060·24 in 2012, 1018·29 in 2013, and 1519·76 in 2014. However, the rate dramatically increased (1·8 times vs 2014) to 2739·51 in 2015 when free cataract screening was available. 500 patients completed the questionnaire. 15 (3·0%) patients refused to respond and 12 (2·4%) patients did not understand the questions asked. The results showed that 2606 (56·5%) respondents did not have any ophthalmic examinations in the preceding 5 years, and 2372 (51·4%) respondents were unaware of cataract before screening. Interpretation: Cataract screening in collaboration with the CDC is a low-cost, highly effective and practicable strategy to disseminate cataract knowledge and eliminate cataract blindness. This screening model offers regional integrated collaborative service based on public health information platform, solves information and service isolation problems, and saves the medical resources. Funding: National Nature Science Foundation of China (No: 81570843).